ANALISIS PEMBAGIAN HAK WARIS ADAT MANDAILING DI DESA SIALANG JAYA BERDASARKAN KOMPILASI HUKUM ISLAM (KHI) - Widya Melati Sukma; Aufa Yumni; Afriza; Muhammad Fadli; Pemi Marto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the authority regarding inheritance rights of the Mandailing Indigenous community in Sialang Jaya Village, which often causes vulnerable problems in family harmony. In this research, the method used is a qualitative method with a phenomenological approach, namely research based on subjective or phenomenological experiences experienced by individuals. Factors that cause disputes include factors of community knowledge about Islamic inheritance law, from the community's perspective, the causal factors are social, educational and cultural levels that can be categorized as low. The implication of this research is the need for socialization to the community regarding the distribution of inheritance as stipulated in the rules based on the Compilation of Islamic Law (KHI).